2023
DOI: 10.1039/d3cp00251a
|View full text |Cite
|
Sign up to set email alerts
|

Multi-structural variational kinetics study on hydrogen abstraction reactions of cyclopentanol and cyclopentane by hydroperoxyl radical with anharmonicity, recrossing and tunneling effects

Abstract: It remains a long-standing vacancy and challenge of predicting accurate reaction kinetics for H-atom abstractions by HO2 radical from cycloalkanes and cyclic alcohols, which plays a fundamental role in both...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…κ ( T ) is the transmission coefficient accounting for tunneling effects using the one-dimensional asymmetric Eckart model. 43 Comparison between the multidimensional small-curvature tunneling (SCT) 44 and zero-curvature tunneling (ZCT), 45 as well as the one-dimensional Eckart approximation, Yang et al 46 concluded that the Eckart transmission coefficients align better with SCT values than with the ZCT method. Taking the H-atom abstraction from cyclopentanol by hydroperoxyl radicals from beta secondary site as an example, the tunneling transmission coefficients for the Eckart approximation are 44.8%, 27.2%, and 12.3% smaller than those from the SCT approximation at 300 K, 500 K, and 1000 K, respectively.…”
Section: Theoretical and Computational Methodsmentioning
confidence: 99%
“…κ ( T ) is the transmission coefficient accounting for tunneling effects using the one-dimensional asymmetric Eckart model. 43 Comparison between the multidimensional small-curvature tunneling (SCT) 44 and zero-curvature tunneling (ZCT), 45 as well as the one-dimensional Eckart approximation, Yang et al 46 concluded that the Eckart transmission coefficients align better with SCT values than with the ZCT method. Taking the H-atom abstraction from cyclopentanol by hydroperoxyl radicals from beta secondary site as an example, the tunneling transmission coefficients for the Eckart approximation are 44.8%, 27.2%, and 12.3% smaller than those from the SCT approximation at 300 K, 500 K, and 1000 K, respectively.…”
Section: Theoretical and Computational Methodsmentioning
confidence: 99%
“…For D13MCH+OH, R5e with the GTS located in the range of −0.36 − −0.26 a 0 shows the strongest variational effect and has the CVT recrossing transmission coefficient being 0.13 at 200 K and 0.68 at 2000 K. For D14MCH+OH, R2 with the GTS located from −0.43 to −0.11 a 0 and R1 with the GTS located from −0.34 to −0.31 show the weakest and the strongest variational effect, respectively as temperature changes from 200 to 2000 K. Generally, this pronounced variational effect is attributed to the vibrational normal mode corresponding to the approach of donor and acceptor atoms, which changes rapidly along the reaction path as the C−H bonds break and the new O−H bonds form. 75,76 In summary, the CVT recrossing transmission coefficients lie in the range of 0.12−0.95 at 200−2000 K, and different abstraction sites have different temperature-dependent variational features. Therefore, the kinetics treatment using the variational transition state theory is indispensable for our studied abstraction reactions.…”
Section: Transmission Coefficientsmentioning
confidence: 97%
“…Hydrocarbons can be classified into several major groups, including alkanes, cycloalkanes (also known as naphthenes), aromatics, and alkenes [ 1 ]. Cycloalkanes, especially those with C5 and C6 rings, are significant constituents of traditional transportation fuels like diesel and gasoline, accounting for approximately 10 to 30% of their composition [ 2 , 3 ]. They also play a crucial role in jet fuels such as Jet-A/Jet-A1/JP-8 and RP-1, making up a considerable portion of their composition [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, their study lacked theoretical kinetics and quantum chemical calculations at lower temperatures. Yang et al [ 3 ] conducted a theoretical study on the H-migration reactions of cyclic alkylperoxy radicals and calculated the high-pressure limit rate constant and pressure-dependent rate constant of different reactions. All reactions are classified into seven reaction types, and these rules may be used in the development of low-temperature kinetic mechanisms for cycloalkanes.…”
Section: Introductionmentioning
confidence: 99%